ANALISIS KELAYAKAN FINANSIAL USAHA AYAM RAS PETELUR SUNJU MANDIRI DI DESA SUNJU KECAMATAN MARAWOLA KABUPATEN SIGI - Tri Fadila; Saharia Kassa; Alimuddin Laapo (Universitas Tadulako, 2017)
This research aimed to analyze the financial feasibility ofthe laying chicken business of Sunju Mandiri. This research was conducted in Sunju Village, Marawola Sub-district, Sigi District from March to April 2017. Determination of respondents in this study was done purposively. Data was analyzed using financial analysis consisting of 4 investment criteria, namely: Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback Periode(PP). The results of this study showed that NPV during the period 2012 to 2016 was IDR 424,088,257, Net B/C was 1.67, IRR was 37.48% and PP was 2 years 7 months. They also indicate that there had been an increase in the price of the laying chicken feed resulting in raised production costs by 32% with the obtained NPV fell to IDR 3,410,596, Net B/C dropped to 1.01, IRR fell to 14.29%, and PP increase to 3.7 years. However, these values still indicate that the laying chicken of Sunju Mandiri is financially feasible business.